The Food Systems Countdown Report 2023: The state of food systems worldwide - Schneider, Kate R.; Fanzo, Jessica; Haddad, Lawrence; Herrero, Mario; Moncayo, Jose Rosero; Herforth, Anna; Remans, Roseline; Guarin, Alejandro; Resnick, Danielle; Covic, Namukolo M.; Béné, Christophe; Cattaneo, Andrea; et al. (Columbia University; Cornell University; Food and Agriculture Organization of the United Nations (FAO); Global Alliance for Improved Nutrition (GAIN), 2023)
Food systems are a foundation of human and planetary well-being and central to achieving the Sustainable Development Goals. Yet they also contribute to ill health, inequity, environmental degradation, and greenhouse gas emissions. These challenges demand urgent food systems transformation. Such a transformation requires understanding the status of food systems across their diverse functions. The Food Systems Countdown Initiative (“the Countdown”) aims to enable this understanding by monitoring the state of food systems transformation through relevant data, independent of any established monitoring processes. Such monitoring can help align decision makers around key priorities, incentivize action, hold stakeholders accountable, sustain commitment by demonstrating progress, and enable course corrections.